A single‐cell RNA labeling strategy for measuring stress response upon tissue dissociation. Issue 2 (27th December 2022) - Neuschulz, Anika; Bakina, Olga; Badillo‐Lisakowski, Victor; Olivares‐Chauvet, Pedro; Conrad, Thomas; Gotthardt, Michael; Kettenmann, Helmut; Junker, Jan Philipp
Abstract: Tissue dissociation, a crucial step in single‐cell sample preparation, can alter the transcriptional state of a sample through the intrinsic cellular stress response. Here we demonstrate a general approach for measuring transcriptional response during sample preparation. In our method, transcripts made during dissociation are labeled for later identification upon sequencing. We found general as well as cell‐type‐specific dissociation response programs in zebrafish larvae, and we observed sample‐to‐sample variation in the dissociation response of mouse cardiomyocytes despite well‐controlled experimental conditions. Finally, we showed that dissociation of the mouse hippocampus can lead to the artificial activation of microglia. In summary, our approach facilitates experimental optimization of dissociation procedures as well as computational removal of transcriptional perturbation response. Synopsis: A new approach shows that RNA labelling can be used to measure the cellular response to tissue dissociation, a major confounding factor in single‐cell transcriptomics. The dissociation response is partially cell‐type specific. Single‐cell RNA labelling allows measuring the cellular dissociation response, a major confounding factor in single‐cell transcriptomics. The dissociation response is comprised of a core signature that is shared across tissue types and replicates as well as sample‐ and cell‐type‐specific programs. The dissociation of the mouse hippocampus can lead to the activation of microglia. Abstract : A new approach shows that RNA labelling can be used to measure the cellular response to tissue dissociation, a major confounding factor in single‐cell transcriptomics. The dissociation response is partially cell‐type specific.